2007
DOI: 10.1021/ja070516j
|View full text |Cite
|
Sign up to set email alerts
|

The Inner-Sphere Process in the Enantioselective Tsuji Allylation Reaction with (S)-t-Bu-phosphinooxazoline Ligands

Abstract: We propose an inner-sphere mechanism explaining the unique performance of the Tsuji asymmetrical allylation reaction using hard prochiral enolate nucleophiles and non-prochiral allyl groups. Using first principles quantum mechanics (B3LYP density functional theory), we find that the pathway for this reaction involves nucleophilic attack followed by interconversion from a five-coordinate Pd complex to a four-coordinate complex. This intermediate is trapped in a potential well and escapes via reductive eliminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
92
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(99 citation statements)
references
References 21 publications
6
92
1
Order By: Relevance
“…12,13,14 Preliminary studies (Scheme 1) suggested that an internal mechanism (i.e. reductive elimination) is a lower-energy pathway than the corresponding external mechanism involving attack of the enolate onto an η 3 -allyl complex; it was later discovered that η 1 -allylpalladium carboxylate 5 was found to be the resting state of the catalyst and that decarboxylation was likely rate-limiting.…”
Section: Stereoablative Transformationsmentioning
confidence: 99%
“…12,13,14 Preliminary studies (Scheme 1) suggested that an internal mechanism (i.e. reductive elimination) is a lower-energy pathway than the corresponding external mechanism involving attack of the enolate onto an η 3 -allyl complex; it was later discovered that η 1 -allylpalladium carboxylate 5 was found to be the resting state of the catalyst and that decarboxylation was likely rate-limiting.…”
Section: Stereoablative Transformationsmentioning
confidence: 99%
“…1c) may interact with the C3–C4 π cloud, placing the nucleophilic Cγ near the dienoate C6. This pathway would be reminiscent of a 3,3′-reductive elimination proposed vis-à-vis enantioselective allyl–allyl coupling with Ni- and Pd complexes 17,18 . A similar reaction mode with an organocopper species has been mentioned in just one instance (again, without experimental or computational support) 19 .…”
mentioning
confidence: 99%
“…Initial mechanistic studies found zero-order kinetic dependence in substrate, which suggests a fast initial reaction between catalyst and substrate and a slow subsequent step, presumably either decarboxylation or protonation of the putative enolate intermediate common to both the protonation and allylic alkylation reactions with this catalyst system. 74 However, in the protonation reaction opposite enolate facial preference was observed for tetralone-and cyclohexanone-derived enolates, whereas in the alkylation reaction consistent enantiofacial selectivity was observed. 70,71,72 This unexpected result suggests a substantial difference in the bond-forming portion of the mechanism.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 97%